Racism towards African American Women in “Hidden Figures” - Jeany Jean Febriani; Tomi Arianto (Islamic State Institute of Bengkulu (IAIN) Bengkulu, 2020)
Racism is issue that still going on in the world. Different race and skin color make some people believe that they have more privilege than others. The issue of racism can be seen from Hidden Figures movie that was addapted from the book with the same title. Hidden Figures by Theodore Melfi is a story about racism towards African American women who worked in NASA during the space race in 1960. In this research, the researcher takes three main characters named Katherine, Dorothy and Merry who get discrimination in their life because they have different race and skin color as a source. Qualitative descriptive method is the method that was used in this research. The tehcnique of collecting data is by watching the movie and reading the book then collect the utterances and dialogue that have racism issue. The aim of this research is to find out racism in what field that happened in America during 1960 espesially in NASA through Hidden Figures. The result of this analysis found that the racism reflected trough discrimination in education, facility, social, and work.